2010
DOI: 10.2337/db10-0179
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Circulating Sex Hormone–Binding Globulin With Metabolic Traits in Humans

Abstract: OBJECTIVERecent data suggested that sex hormone–binding globulin (SHBG) levels decrease when fat accumulates in the liver and that circulating SHBG may be causally involved in the pathogenesis of type 2 diabetes in humans. In the present study, we investigated mechanisms by which high SHBG may prevent development to diabetes.RESEARCH DESIGN AND METHODSBefore and during a 9-month lifestyle intervention, total body and visceral fat were precisely measured by magnetic resonance (MR) tomography and liver fat was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
127
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 53 publications
13
127
2
2
Order By: Relevance
“…In this respect, they highlighted that loss of body weight induced by changes in diet and physical activity may result in an increase of circulating SHBG. In this respect, we showed that loss of liver fat content most strongly correlated with increase in circulating SHBG during a lifestyle intervention (2,3). This is in agreement with published information indicating that reduction in hepatic inflammatory signaling and hepatic lipogenesis mediates this increase (5).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In this respect, they highlighted that loss of body weight induced by changes in diet and physical activity may result in an increase of circulating SHBG. In this respect, we showed that loss of liver fat content most strongly correlated with increase in circulating SHBG during a lifestyle intervention (2,3). This is in agreement with published information indicating that reduction in hepatic inflammatory signaling and hepatic lipogenesis mediates this increase (5).…”
supporting
confidence: 90%
“…In our studies, circulating SHBG correlated stronger with liver fat content, both in cross-sectional and longitudinal analyses, than with total body and visceral fat mass or whole-body insulin sensitivity (2,3). Interestingly in their most recent article, Hedderson and colleagues (4) found in the same study that increased g-glutamyl transferase levels were associated with increased odds of the development of GDM.…”
mentioning
confidence: 52%
“…However, this relationship of SHBG with QOL disappeared in most of the subscales after correction for BMI. The level of SHBG varies with nutritional status (and thus BMI), age and sex hormones, which interferes with its use as a sensitive parameter of TH action (40). As the majority of hypothyroid patients are female (with fluctuations in estrogen levels during life), SHBG is not a suitable marker of TH status.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is supported by an in vitro experiment in which human HepG2 hepatoblastoma cells produce less SHBG when treated with insulin (11,12). However, a few of the subsequent studies have found no direct association between SHBG and insulin or insulin resistance (13,14,15). A recent study by Selva et al (16) reports that SHBG is not regulated by insulin but rather repressed by monosaccharide-induced lipogenesis in human HepG2 cells.…”
Section: Introductionmentioning
confidence: 98%